Wat is charismatiese teologie? 'n Oorsig oor resente verwikkelinge - J Theron (Acta Theologica)
The term "charismatic" means different things to different people. From one perspective it is clear that the growing number of charismatic theologies have different characteristics. However, it should be noted that the Charismatic Movement as such is too young to produce a distinctive theology. Many charismatics belong to mainline churches and these people do not want to develop a new theology but rather prefer to reinterpret some aspects of their own tradition in terms of new-found insights and experiences. On the other hand, some trends and emphases are developing which can be identified and classified separately. In order to do this the historical roots of the Movement as well as streams that influence the development of a systematic theology are looked at. The main characteristics of the most influential groups and the thoughts of their leaders are discussed.